2019
DOI: 10.3897/phytokeys.134.38238
|View full text |Cite
|
Sign up to set email alerts
|

Defining phylogenetic relationship of Nepeta x tmolea and its parents via DNA barcoding

Abstract: Nepeta viscida and N. nuda subsp. nuda and N. × tmolea were examined in this study. Mainly fresh leaf pieces, dried with silica grains, were used for DNA extraction procedures via DNA isolation kits. Standard PCR techniques were executed using three different primer sets (one nuclear DNA region (nrITS) and two chloroplast DNA regions (rpl32-trnL and trnA(Leu)-trnA(Phe)-trnL-F). DNA sequences were analysed and evaluated using different molecular approaches and software. Consequently, the inconstant molecular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The plastome data has been successfully used to estimate family-wide relationships within Lamiaceae with sufficient resolution at subfamily and tribe levels (Li et al, 2016 ; Zhao et al, 2021 ). The previous studies highlight the relevance of nuclear non-coding ITS DNA sequences to infer evolutionary relationships at intrageneric taxonomic ranks of Nepeta species often correlating with floral and pollen morphological characters (Jamzad et al, 2003a ; Al-Qurainy et al, 2014 ; Özcan, 2019 ; Alzeibr et al, 2020 ). Based on ITS markers, Jamzad et al ( 2003a ) have shown that Nepeta is defined as monophyletic consisting of two large clades with four subclades.…”
Section: Discussionmentioning
confidence: 99%
“…The plastome data has been successfully used to estimate family-wide relationships within Lamiaceae with sufficient resolution at subfamily and tribe levels (Li et al, 2016 ; Zhao et al, 2021 ). The previous studies highlight the relevance of nuclear non-coding ITS DNA sequences to infer evolutionary relationships at intrageneric taxonomic ranks of Nepeta species often correlating with floral and pollen morphological characters (Jamzad et al, 2003a ; Al-Qurainy et al, 2014 ; Özcan, 2019 ; Alzeibr et al, 2020 ). Based on ITS markers, Jamzad et al ( 2003a ) have shown that Nepeta is defined as monophyletic consisting of two large clades with four subclades.…”
Section: Discussionmentioning
confidence: 99%